The Symbiotic Relationship between the Antarctic Limpet, Nacella concinna, and Epibiont Coralline Algae - Boongho Cho; Hyeonmi Bae; Taewon Kim (Journal of Marine Science and Engineering, 2022)
The Antarctic limpet, Nacella concinna, is one of the most abundant benthic marine invertebrates found in the intertidal zone of King George Island, Antarctica. The shell of N. concinna is often encrusted with the coralline algae Clathromorphum obtectulum. In this study, to reveal the relationship between the limpet and coralline algae, we examined how the coralline algae affect the physical condition (survival and health) and morphology of the limpet. We cultured the limpets for 22 days and compared mortality, weight, condition factor (CF), fatty acid content, and the structure of the shell surface between limpets both with and without coralline algae in the laboratory. We also measured the environmental factors (i.e., temperature, pH, and salinity) of the seawater at each sampling site and the CF of the limpets and correlated them with coverage of coralline algae. The presence of coralline algae significantly increased the mortality of the limpets by 40% and the shell weight by 1.4-fold but did not affect the CF. Additionally, coralline algae altered the fatty acid profiles related to the limpet’s lipid metabolism (saturated fatty acids (SFA) and some polyunsaturated fatty acids (PUFA)). Specifically, C16:0, C17:0, C18:0, and total SFA increased, whereas C18:2 and C18:3 decreased. However, observations with a scanning electron microscope showed that shell damage in limpets with coralline algae was much less than in limpets without coralline algae, suggesting that coralline algae may provide protection against endolithic algae. The area of coralline algae on the limpet shell was positively correlated with the pH and temperature of the seawater. The results suggest that although coralline algae are generally assumed to be parasitical, the relationship between N. concinna and coralline algae may change to mutualism under certain conditions.